1999
DOI: 10.1001/archneur.56.8.943
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Heterogeneity of Autosomal Recessive Spastic Paraplegias

Abstract: Although autosomal recessive HSP represents a heterogeneous group of diseases, some phenotypes can be defined by analyzing a large group of patients. The fact that only one Algerian family was linked to chromosome 8 suggests that this is a rare localization even in kindreds with the same ethnic background. Linkage to chromosome 16 was found in 2 clinically diverse Portuguese kindreds, illustrating that this locus is also rare and may correspond to different phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
3
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 22 publications
8
64
3
1
Order By: Relevance
“…Similar to other communities with high consanguinity, 9,10 we found that AR HSP inheritance is predominant in Sudan. However, in our series, the complex phenotype is predominant (84%), which is in disagreement with Coutinho et al 9 who elicited a predominant pure phenotype, but in agreement with a study in South Tunisia 10 that reported 69% of complex cases.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to other communities with high consanguinity, 9,10 we found that AR HSP inheritance is predominant in Sudan. However, in our series, the complex phenotype is predominant (84%), which is in disagreement with Coutinho et al 9 who elicited a predominant pure phenotype, but in agreement with a study in South Tunisia 10 that reported 69% of complex cases.…”
Section: Discussionsupporting
confidence: 87%
“…However, in our series, the complex phenotype is predominant (84%), which is in disagreement with Coutinho et al 9 who elicited a predominant pure phenotype, but in agreement with a study in South Tunisia 10 that reported 69% of complex cases. Sudanese families with AR HSP showed a high frequency of SPG11 variants (~13%) in conformity with other populations.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Clinically and genetically, AR-HSP with thin corpus callosum was poorly studied in Caucasian population. Two Caucasian families were linked to chromosome 15q13-15 10 , and one kindred was linked to chromosome 16 11 .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there was only 4 Caucasian families of AR-HSP with thin corpus callosum described, including one North American 10 , one Italian 10 , one Spanish 4 , and one Portuguese family 11 . In contrast, more than 20 families of AR-HSP have been described in Japan.…”
Section: Discussionmentioning
confidence: 99%